The prevalence of anti-C1q antibodies in black South Africans with systemic lupus erythematosus and their clinical significance - Makda, Mohamed Amin (My University, 2013)
INTRODUCTION: Several studies have shown an association of anti-C1q antibodies (abs) with systemic lupus erythematosus (SLE) nephritis and disease activity. The aim of this study is to determine the relevance of the anti-C1q abs and the C1q levels, in Black South Africans with SLE and their relevance to disease activity and/or organ damage, specifically renal disease. METHODS: Serum anti-C1q abs and C1q levels were measured in 96 SLE patients who were also assessed for disease activity, using the SELENA Systemic Lupus Erythematosus Disease Activity Index (SLEDAI), and organ damage as measured by the Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC) Damage Index. Furthermore patients were assessed for the presence of an active urine sediment as evidenced by otherwise unexplained proteinuria, haematuria or cellular casts. Serum anti-C1q abs was measured by a commercial Elisa kit and serum C1q by immunoelectrophoresis. RESULTS: Of the 96 patients; the majority, 87 were female (90.65%), with a mean (SD) age and disease duration (SD) of 38.1 (13.0) years and 4.2 (4.4) years respectively. An active urine sediment was found in 21 (21.88%) patients. Elevated anti-C1q abs were present in 12 (12.50%) of the patients and 7 (14.29%) of the patients with renal involvement. Serum anti-C1q abs levels correlated significantly with SELENA SLEDAI scores (p=0.004, r =0.41).Anti-C1q abs levels were significantly higher in patients with an active urine sediment (p= 0.007). C1q levels were decreased in 17/96 (17.71%) patients and 11/49 (22.45%) patients with renal involvement. No associations with any other clinical features were observed. CONCLUSION: The findings indicate that in Black South Africans with SLE, although elevated anti-C1q abs levels were present in only a small minority of patients, the abs were associated with SLE global activity as determined by the SELENA SLEDAI and to the presence of an active urine sediment. These findings suggest that anti-C1q abs are a potential bio-marker of disease activity, especially active renal disease.
Keywords: Lupus Erythematosus, Systemic